Simple Rapid Production of Calcium Acetate Lactate from Scallop Shell Waste for Agricultural Application - Sorakit Mongkol; Somkiat Seesanong; Banjong Boonchom; Nongnuch Laohavisuti; Wimonmat Boonmee; Somphob Thompho; Pesak Rungrojchaipon (My University, 2025)
Calcium acetate lactate (CAL) was rapidly synthesized for the first time using the reaction between the scallop shell-derived calcium carbonate (CaCO3) and the binary phase of acetic and lactic acids. Calcium acetate (CA) and calcium lactate (CL) synthesized from the reaction of scallop shell-derived CaCO3 with each acid by similarity routes are compared with the obtained CAL product. The production yields are 88.24, 79.17, and 96.44%, whereas the solubilities are 93.77, 90.18, and 95.08% for CA, CL, and CAL, respectively. All the synthesized CA, CL, and CAL samples were characterized and confirmed by X-ray fluorescence (XRF) to examine the calcium main element and other impurities of minor elements, X-ray diffraction (XRD) to investigate the crystallography, Fourier transform infrared (FTIR) to characterize the vibrational characteristics of the functional groups, scanning electron microscope (SEM) to observe the sample morphologies, and the thermogravimetric analysis (TGA) to investigate the thermal decomposition processes of samples. The experimental results pointed out that the synthesized CA, CL, and CAL were the monohydrate, pentahydrate, and dihydrate forms with chemical formulae of Ca(CH3COO)2·H2O, Ca(CH3CHOHCOO)2·5H2O, and Ca(CH3COO)(CH3CHOHCOO)·2H2O, respectively. The final thermal decomposition product of all calcium compounds was calcium oxide (CaO). The CAL sample’s vibrational characteristics, crystal phases, and morphologies show the binary acetate and lactate anion phases, confirming the new binary anionic calcium acetate lactate obtained. In conclusion, this research proposes an easy and low-cost technique to prepare a new valuable CAL compound using scallop shell waste as a cheap and renewable calcium source.
Keywords: Thermogravimetric analysis; Calcium silicate; Calcium Carbonate Crystallization and Inhibition